Implementation of Internal Control in Accounting Information Systems Based Online - R Riyanti; D Dassaad; Dyah Palupi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The background of this research is how to make an accounting information system that is initially offline will be made online, while the problems and methods raised in this research will be explained in the abstract. The problem raised in this research is how to make the existing system at PT ARS COMPUTINDO ABADI into an online system that can assist leaders and subordinates in managing the company so that regular and periodic online checks can be carried out. The method used in this study is to use the 4K method, namely the boundary control, input control, processing control, and output control methods. Where the method is, it can be seen how the data entered into the system is processed and generated. The purpose of this research is how to find out whether the online system that is applied to the accounting information system, in a company works optimally after being analyzed, the data obtained are the results are much better, and company data can be seen in general and free but conditional and the leaders can do internal control anywhere and anytime.